Metabolic therapy of multimorbid patients with arterial hypertension and inflammatory diseases of a parodentium - Yu. A. Sycheva; I. A. Gorbacheva; L. Yu. Orekhova; P. S. Shabak-Spassky; L. P. Egorova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
AH is accompanied by deep metabolic and functional violations in organism tissue, including also the parodentium. The special attention is drawn by efficiency of the metabolic preparations possessing multimodal actions and allowing carrying out therapy of a number of states. The preparation of L-carnitine which is a perspective remedy for patients with AH associated with Inflammatory Deseased of Parodentium belongs to such means. In work studying of clinical efficiency and mechanisms action of L-carnitine in patients with AH and inflammatory diseases of parodentium was carried out. 70 patients with AH associated with IPD were divided into groups by way of simple randomization: a group with inclusion of a L-carnitine into the treatment and a control group, receiving only standard therapy. In the conducted research high antioxidant activity of the preparation is confirmed and the effect of L-carnitine normalizing tissue microcirculation is noted.